Public awareness, attitudes, and motivation toward biobanks: a survey of China - Mingtao Huang; Lanyi Yu; Xiaonan Wang; Kun Li; Jichao Wang; Xinrui Cheng; Xiaomei Zhai (BMC Medical Ethics)
Abstract Background Biobanks are vital for advancing medical research, and public participation is a crucial determinant of their success. This study uses a survey to assess the awareness, attitudes, and motivation of the public in China with regard to participating in biobanks. Methods We conducted an online survey that yielded 616 responses from participants with diverse demographic backgrounds. The survey included questions on the respondents’ awareness of biobanks, their attitudes toward them, their preferences with regard to consent, and their concerns. Results The results of the survey revealed that 57.95% of the respondents were aware of biobanks. Altruism was the respondents’ primary motivation for participation in biobanks. Their preferences for models of consent varied. The respondents raised concerns about the commercialization of biobanks (56.66%) and data privacy (55.84%). Notably, only 37.01% of the respondents were concerned about the risk of discrimination in biobanks, where this was lower compared with the results for populations in Western countries. Conclusions This study provides valuable insights into the Chinese public’s awareness of and attitudes toward biobanks. To foster public trust and enhance participation, biobanks should prioritize transparent and continual communication to ensure that the participants are well informed about the use and protection of the samples that they have donated. Future research should explore the influence of cultural nuances to develop strategies that address specific concerns and ethical challenges in the context of public participation in biobanks.